EFEKTIVITAS EDUKASI DISLOKASI BERBASIS AUDIOVISUAL TERHADAP PENINGKATAN PENGETAHUAN PERTOLONGAN PERTAMA PADA REMAJA - Muhammad Deri Ramadhan Ramadhan; Fanny Pebiolla; Dewi Heryani; Nazwa Nur Hanifah; Khumaira Khalisa Hadi Hadi; Lingga Dini; Mia Amelianti; Melisa Dwi; Muhamad Nasrul (Institut Kesehatan Yarsi Mataram, 2026)
Dislocation is a joint injury that commonly occurs among adolescents due to physical activities and accidents in the school environment. Limited knowledge of first aid management for dislocation may lead to inappropriate initial handling and increase the risk of further injury. This community service activity aimed to improve vocational high school students’ knowledge of dislocation and first aid through audiovisual-based education. The activity was conducted at SMK Tunas Bangsa Ngamprah and involved 53 students. The implementation method included health education using PowerPoint presentations, educational videos, and posters, as well as knowledge evaluation through pre-test and post-test. The evaluation results showed an increase in the mean knowledge score from 45.5 in the pre-test to 93.5 in the post-test. This result indicates an improvement in students’ understanding of dislocation, its signs and symptoms, and appropriate first aid measures after participating in the educational activity. Audiovisual-based dislocation education can be used as a supportive approach in school health programs to enhance adolescents’ preparedness in dealing with musculoskeletal injuries.